Use of an Isolated Facultative Thermophilic Alkaline Desulfuricant Strain for Decomposition of Thiosulfate - Zhang, Jianbin; Zhang, Yongfeng; Bai, Jie; Wei, Xionghui; Zhao, Yuzhu; Wu, Hai; Xia, Xiaohua (Asian Journal of Chemistry, 2011)
The use of a desulfurization strain BYD-3, which isolates from soil and belongs to the thermophilic alkaline desulphuricant strain, for the decomposition of thiosulfate is reported. The strain can utilize thiosulphate as sulfur source and various organic compounds as carbon source. The colony of the strain is ivory-white and becomes primrose-yellow with protracting cultivated time. The cells of BYD-3 are motive and Gram negative. According to GenBank data, 16s rDNA results of BYD-3 are in good agreement with Pseudomonas stutzeri (100 %). For BYD- 3, the optimum growth temperature is determined at 40 ºC, the optimum pH is found at 8.5 and the optimum rocking speed of sorting table is confirmed at 150 rpm. Under the optimum condition, the cells of BYD-3 can live for 36 h. Meanwhile, the concentration of thiosulphate in the media containing the cells of BYD-3 was decreased by 0.128 g/L from 3.2 g/L (percentage loss of content 96 %) in 28 h, meanwhile, sulfide was formed. These results suggest that the strain has potential application to the regeneration of the industrial solution containing thiosulphate.